Waterborne protozoan pathogens in environmental aquatic biofilms: Implications for water quality assessment strategies. (April 2020) - Masangkay, Frederick R.; Milanez, Giovanni D.; Tsiami, Amalia; Hapan, Freida Z.; Somsak, Voravuth; Kotepui, Manas; Tangpong, Jitbanjong; Karanis, Panagiotis
Abstract: Biofilms containing pathogenic organisms from the water supply are a potential source of protozoan parasite outbreaks and a significant public health concern. The aim of the present study was to demonstrate the simultaneous and multi-spatial occurrence of waterborne protozoan pathogens (WBPP) in substrate-associated biofilms (SAB) and compare it to surface water (SW) and sediments with bottom water (BW) counterparts using manual filtration and elution from low-volume samples. For scenario purposes, simulated environmental biofilm contamination was created from in-situ grown one-month-old SAB (OM-SAB) that were spiked with Cryptosporidium parvum oocysts. Samples were collected from the largest freshwater reservoirs in Luzon, Philippines and a University Lake in Thailand. A total of 69 samples (23 SAB, 23 SW, and 23 BW) were evaluated using traditional staining techniques for Cryptosporidium, and Immunofluorescence staining for the simultaneous detection of Cryptosporidium and Giardia . WBPP were found in 43% SAB, 39% SW, and 39% BW of the samples tested in the present study with SAB results reflecting SW and BW results. Further highlights were demonstrated in the potential of using low-volume samples for the detection of parasites in source water. Scanning electron microscopy of OM-SAB samples revealed a naturally-associated testate amoeba shell, while Cryptosporidium oocysts spiked samples provided a visual profile of what can be expected from naturally contaminated biofilms. This study provides the first evidence for the simultaneous and multi-spatial occurrence of waterborne protozoan pathogens in low-volume aquatic matrices and further warrants SAB testing along with SW and BW matrices for improved water quality assessment strategies (iWQAS). Graphical abstract: Image 1 Highlights: Analysis of aquatic biofilms increased the detection of protozoan (oo)cysts. Biofilms acted as biological reservoirs for Cryptosporidium and Giardia (oo)cysts. Cryptosporidium and Giardia (oo)cysts were detected in low-volume samples of 50 mL. 50 mL sampling permits multiple sampling, reproducibility, and lower test cost. 50 mL is the lowest water volume reported for the detection of Cryptosporidium. Abstract : Analysis of biofilms along with surface water and sediments in environmental aquatic systems lead to improved detection and isolation of waterborne protozoan pathogens.